2016
DOI: 10.1080/17843286.2016.1168065
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic panniculitis as a paraneoplastic phenomenon of a pancreatic acinar cell carcinoma

Abstract: We present the case of a 59-year-old patient admitted with extreme painful erythematous subcutaneous nodules of the lower extremities in association with arthritis and peripheral eosinophilia. Upon skin biopsy, the diagnosis of pancreatic panniculitis was made. On further investigation, an underlying acinar cell type pancreas carcinoma was revealed. This clinical case does illustrate how a seemingly innocuous skin condition may herald an underlying malignant disease. The presence of pancreatic panniculitis sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Including the current case, a total of 10 ACC patients with germline BRCA2 mutations have now been reported (Table 2). 7,[17][18][19][20][21] Loss of the wild-type BRCA2 allele, observed in all cases with known zygosity, 7,17 supports the causal relation between BRCA2 germline mutation and the onset of ACC. Moreover, literature review showed that somatic BRCA2 alterations occur in about 12% of ACCs.…”
Section: Discussionmentioning
confidence: 56%
See 4 more Smart Citations
“…Including the current case, a total of 10 ACC patients with germline BRCA2 mutations have now been reported (Table 2). 7,[17][18][19][20][21] Loss of the wild-type BRCA2 allele, observed in all cases with known zygosity, 7,17 supports the causal relation between BRCA2 germline mutation and the onset of ACC. Moreover, literature review showed that somatic BRCA2 alterations occur in about 12% of ACCs.…”
Section: Discussionmentioning
confidence: 56%
“…Literature review of ACC in patients with a germline BRCA2 mutation identified nine additional cases (Table 2). 7,[17][18][19][20][21] The mean age at diagnosis was 62 years (SD: 8.7; range: 50-78), which is similar to sporadic cases. 4 Including the current patient, seven males (67%) and three females (33%) were identified, resulting in male-to-female ratio of 2.3:1, corresponding to the male predominance in sporadic ACC.…”
Section: Literature Review Of Pancreatic Accs Associated With Germlinmentioning
confidence: 56%
See 3 more Smart Citations